Living conditions and the mental health and well-being of refugees: Evidence from a large-scale German panel study - Lena Walther; Lukas M. Fuchs; Jürgen Schupp; Christian von Scheve (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
The mental health and well-being of refugees are both prerequisites for and indicators of social integration. Using data from the first wave of a representative prospective panel of refugees living in Germany, we investigated how different living conditions, especially those subject to integration policies, are associated with experienced distress and life satisfaction in newly-arrived adult refugees. In particular, we investigated how the outcome of the asylum process, family reunification, housing conditions, participation in integration and language courses, being in education or working, social interaction with the native population, and language skills are related to mental health and well-being. Our findings show that negative and pending outcomes of the asylum process and separation from family are related to higher levels of distress and lower levels of life satisfaction. Living in communal instead of private housing is also associated with greater distress and lower life satisfaction. Being employed, by contrast, is related to reduced distress. Contact to members of the host society and better host country language skills are also related to lower levels of distress and higher levels of life satisfaction. Our findings offer insights into correlates of refugees' well-being in the first years after arrival in a host country, a dimension of integration often overlooked in existing studies, thus having the potential to inform decision-making in a highly contested policy area.
Keywords: 330